Skull Anatomy of the Bizarre Crocodylian Mourasuchus nativus (Alligatoridae, Caimaninae) - Bona, Paula (2012)
Mourasuchus is a Miocene alligatorid endemic to South America, and is represented by four species. Together with the closely related Purussaurus, it is a peculiar crocodylian taxon of neogene Caimaninae and one of the most bizarre forms among eusuchian crocodiles. The phylogenetic relationships between Mourasuchus species have not been explored, and detailed skull descriptions are scarce. The goal of this study is to provide new data on skull morphology and cranial recesses in Mourasuchus nativus, including a new tomography analysis (3D modeling). We observed that several diagnostic characters of Purussaurus, such as lack of contact between the nasal and lacrimal, separation of the nasal and frontal by the prefrontals, and the posterior dorsal margin of the skull table, are shared with Mourasuchus. M. nativus is characterized by the presence of solid transverse squamosal eminences, large posttemporal fenestrae, and a quadrate laterocaudal bridge separating V2-V3 trigeminal openings. Compared with other crocodylians, the endocast of M. nativus is similar in shape but quite sigmoid in lateral view, the canal of the supraorbital ramus of V2 is more vertically oriented, the thick tympanic branch canal opens in a large foramen aligned with trigeminal foramen, and the canal of the vagal (X) tympanic ramus is also very wide. Contrary to extant alligatorids, the median pharyngeal recess remains paired throughout its course and only connects its opposite fellow near the external ventral opening. The knowledge of the internal skull anatomy of Mourasuchus contributes to the understanding of the general morphology of alligatorids, Caimaninae, and their variation.